ECOLOGICAL STABILIZATION OF URBAN ECOSYSTEMS THROUGH LANDSCAPE-ECOLOGICAL PLANNING: METHODOLOGICAL ASPECT - Ласло, Оксана (SWorldJournal, 2020)
A necessity is in process examined ecologically optimizations and stabilizing of the ecological state of the municipal systems in the context of the landscape ecological planning. The brought methodological aspects over give an opportunity to carry out op